Physicochemical properties of organic non-linear optical (NLO) DL-alanine maleate (DLAM) single crystals. (April 2014) - Rathika, A.; Guru Prasad, L.; Ganapathi Raman, R.
Abstract : New organic DL-alanine maleate single crystals have been grown using slow evaporation solution growth technique. The solubility of grown material was determined using water as solvent. Single crystal X-ray diffraction reveals that the grown crystal crystallises in orthorhombic system with non-centrosymmetric space group. Functional groups and their modes of vibration were studied by Fourier transform infrared and Raman spectrum. Thermal stability and nature of decomposition were studied using thermogravimetric analysis/differential thermal analysis plot. The grown crystal shows low absorption behaviour in the entire visible region. A dielectric study was also a study of the distribution of charges within the crystal. Non-linear optical property of the crystal was confirmed using the Kurtz and Perry powder technique.